Development of BacMam Induced Hepatitis E Virus Replication Model in Hepatoma Cells to Study the Polyprotein Processing - Kumar, Manjeet; Hooda, Preeti; Khanna, Madhu; Patel, Utkarsh; Sehgal, Deepak (Frontiers in Microbiology, 2020)
The processing of polyprotein(s) to form structural and non-structural components remains an enigma due to the non-existence of an efficient and robust Hepatitis E Virus (HEV) culture system. We used the BacMam approach to construct an HEV replication model in which the HEV genome was cloned in the BacMam vector under the CMV promoter. The recombinant BacMam was used to infect Huh7 cells to transfer the HEV genome. HEV replication was authenticated by the presence of RNAs of both the polarity (+) and (-) and formation of hybrid RNA, a replication intermediate. The presence of genes for Papain-like Cysteine Protease (PCP), Methyltransferase (MeT), RNA dependent RNA polymerase (RdRp), and ORF2 was confirmed by PCR amplification. Further, the infectious nature of the culture system was established as evidenced by the cross-infection of uninfected cells using the cell lysate from the infected cells. The HEV replication model was validated by detection of the ORF1 (Open Reading Frame1) encoded proteins, identified by Western blotting and Immunofluorescence by using epitope-specific antibodies against each protein. Consequently, discrete bands of 18, 35, 37, and 56 kDa corresponding to PCP, MeT, RdRp, and ORF2 respectively were seen. Besides demonstrating the presence of non-structural enzymes of HEV along with ORF2, activity of a key enzyme, HEV-Methyltransferase has also been observed. A 20% decrease in the replicative forms of RNA could be seen in presence of 100uM Ribavirin after 48 hours of treatment. The inhibition gradually increased from 0 to 24 to 48 hour post-treatment. Summarily, infectious HEV culture system has been established, which could demonstrate the presence of HEV replicative RNA forms, the structural and non-structural proteins and the Methyltransferase in its active form. The system may also be used to study the mechanism of action of Ribavirin in inhibiting HEV replication and develop a therapy.